2018 IEEE International Professional Communication Conference (ProComm) 2018
DOI: 10.1109/procomm.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Entertaining or Functional: An Analysis of Visuals in Chinese and Western Household Appliance Manuals

Abstract: In today's global world, understanding local user preferences becomes an increasingly essential skill, especially for technical communicators who design products for people in other cultures. This study attempts to analyze and compare visuals in Chinese and Western manuals because visuals play an essential role in manuals. Based on a systematically designed coding scheme, we analyzed 50 Western and 50 Chinese household product manuals (1895 pages in total) designed in their own cultures and published after 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…While larger demand for eating outdoor is economically viable for the post-recovery phase of the outbreak, it seems that people generally prefer to recover from several months of constantly cooking and eating inside their households. The same pattern is also seen for household entertainment [72,73] that constitutes a relationship between indoor stay and activities. For instance, household entertainment was almost tripled during the lockdown period but is reduced to its normal figures after the lockdown.…”
Section: Main Impacts On Household 'Cooking' and 'Entertainment'supporting
confidence: 58%
“…While larger demand for eating outdoor is economically viable for the post-recovery phase of the outbreak, it seems that people generally prefer to recover from several months of constantly cooking and eating inside their households. The same pattern is also seen for household entertainment [72,73] that constitutes a relationship between indoor stay and activities. For instance, household entertainment was almost tripled during the lockdown period but is reduced to its normal figures after the lockdown.…”
Section: Main Impacts On Household 'Cooking' and 'Entertainment'supporting
confidence: 58%
“…However, the results of the previously mentioned content analysis could not confirm these earlier results: no differences were found between the number of visuals and the extent to which visuals are integrated with the text. The results of this recent study, however, showed that different types of visuals are used in Chinese user instructions than in Western user instructions [10,12]. More cartoon-like figures are used in Chinese manuals and more detailed pictures of how a task should be performed are found in Western manuals.…”
Section: Literature Review: Differences Between Chinese and Western Umentioning
confidence: 80%